PENENTUAN KADAR POLIFENOL EKSTRAK TEH KEMASAN DENGAN METODE REMASERASI MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Hadi Barru Hakam Fajar Siddiq, Jati Riyuwani, Rizka Della Yunita Dewi (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2017)
The purpose of this research is determine the polyphenol content of various brand of packaged tea. Sample were used five sample. Polyphenol compounds of packaged tea were extracted using remaseration method with ethanol 70%. Qualitative test were used using FeCl3 reagent and quantitative test polyphenol content were determined using UV-Vis spectrophotometry method with Folin Ciocalteau reagent. Galic acid was used as comparator in this research. The result of qualitative test is all sample of brewed tea containing polyphenol. Polyphenol content sample A, B, C, D, and E with remaseration method were respectively 0,541; 0,557; 0,474; 0,557; and 0,428%(b/b).Keyword: packaged tea, polyphenol, remaseration, UV-Vis spectrophotometryThe purpose of this research is determine the polyphenol content of various brand of packaged tea. Sample were used five sample. Polyphenol compounds of packaged tea were extracted using remaseration method with ethanol 70%. Qualitative test were used using FeCl3 reagent and quantitative test polyphenol content were determined using UV-Vis spectrophotometry method with Folin Ciocalteau reagent. Galic acid was used as comparator in this research. The result of qualitative test is all sample of brewed tea containing polyphenol. Polyphenol content sample A, B, C, D, and E with remaseration method were respectively 0,541; 0,557; 0,474; 0,557; and 0,428%(b/b).Keyword: packaged tea, polyphenol, remaseration, UV-Vis spectrophotometryPENDAHULUANTeh merupakan minuman yang dapat diterima oleh